Authenticity Of Characters Portrayal In Islamic Films: A Study On The Message - Osama Kanaker; Rosidayu Sabran; Suria Hani A. Rahman; Salah Mohamed Zaki Ibrahim (Universiti Sains Islam Malaysia, 2024)
Muslim communication academicians and writers had been calling for portraying Islam in drama. This call has been answered by some directors and producers who attempted to produce drama about Islam. However, these attempts are facing criticism due to misportrayal of the original characters in the drama produced. The objectives of this study are to identify the main characters of The Message and to test the authenticity of the portrayal of the characters of The Message. The main finding of the study is that the characters of The Message were misportrayed. The misportrayal took place on the psychological dimension of the characters. Some of the Muslim characters were degraded, while some non-Muslim characters were elevated. The misportrayal of the characters lies in their voice tone that shows Muslims as barbaric and hegemonic on the first hand, while on the other hand non-Muslims are portrayed as wise and logical people.